One-Year Histopathological Audit of Thyroid Lesions at Tertiary Care Hospital of Peshawar - Attaullah, Mir; Shah, Hamid Ullah (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective To know the number of various thyroid lesions both neoplastic and non-neoplastic in a tertiary care hospital of Peshawar. Methodology It was a retrospective record-based study conducted at Lady reading Hospital (LRH) Peshawar Khyber Pakhtunkhwa. Histopathological reports of all the thyroidectomy specimens received from 1st January 2019 to 31st December 2019 in the Department of Pathology were included in this study. Data regarding patient’s age, sex, type of thyroidectomy and histopathological diagnosis was collected from the record of the laboratory, recorded into Microsoft excel and analyzed by statistical methods. Results This study included a total of 120 thyroidectomy. The highest frequency of lesions was seen in the fourth and fifth decades (32.74%) with a female predominance (88.38%). Non neoplastic lesions were 106 (88.7%) while neoplastic lesions were 14 (11.7%). Nodular colloid goiter was the commonest non neoplastic lesion while papillary thyroid carcinoma was the most common neoplastic lesion. Follicular adenoma was the most common benign lesion. Conclusion Histopathological audit, of various thyroid lesions is important both for surgeons and pathologists to make them aware about the common and uncommon thyroid lesions in the setup. Moreover, it can also be used for preventive strategies for various thyroid diseases. Key words Thyroidectomy, thyroid lesions, neoplastic, thyroiditis, papillary carcinoma